FORMULASI EKSTRAK TONGKOL JAGUNG (Zea mays L.) SEBAGAI TABIR SURYA DALAM SEDIAAN LOTION UNTUK WAJAH - Maringan Silitonga; Pandapotan Nasution; Cut Masyithah Thaib; Mei Revolinda Haloho (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Corn cobs (Zea mays L.) can be used as sunscreen because it contains phenolic compounds. The purpose of this study was to determine the characteristics of the physical and chemical properties of sunscreen lotion preparations of corncob ethanol extract and the formula and concentration that had the highest effectiveness in the value of Sun Protection Factor (SPF). The lotion was chosen because it is a topical preparation that is often used by the community. Corn cob powder was extracted by the maceration method. The results were formulated with extract concentrations, formulation I (5%), formulation II (10%), and formulation III (15%). The three formulas were tested for organoleptic, pH test, homogeneity, and lotion type. The resulting data were analyzed descriptively. The results showed that all formulas with varying concentrations of extracts had good physicochemical characteristics during storage based on the results of pH, homogeneity, organoleptic, and emulsion-type tests. Corncob ethanol extract sunscreen lotion in Formula 1 (5%) has an SPF value of 2 (UV-A rays) and an SPF value of 7 (UV-B rays). Formula 2 (10%) has an SPF value of 2,3 (UV-A rays) and has an SPF value of 9 (UV-B rays) and Formula 3 (15%) has an SPF value of 3 (UV-A rays) and has a value of SPF 12 (UV-B Rays).